Repurposing human Aurora kinase inhibitors as leads for anti-protozoan drug discovery - Patel, Gautam (2014)
Hesperadin, an established human Aurora B inhibitor, was tested against cultures of Trypanosoma brucei, Leishmania major, and Plasmodium falciparum, and was identified to be a potent proliferation inhibitor. A series of analogs was designed and tested to establish the initial structure-activity relationships for each parasite. In this study, we identified multiple non-toxic compounds with high potency against T. brucei and P. falciparum with good selectivity. These compounds may represent an opportunity for continued optimization.